Analisis Pengaruh Net Premium Growth Ratio, Solvency Margin Ratio, Underwriting Ratio, dan Investment Yield Ratio Terhadap Return On Equity - Sari, Juliani Lisma; Alfiyah, Nasya; Siregar, Vita Evelini Handayani; Mardan, Novian i (Eqien - Jurnal Ekonomi dan Bisnis, 2024)
This research is a study conducted to analyze the effect of the Net Premium Growth Ratio, Solvency Margin Ratio, Underwriting Ratio, and Investment Yield Ratio on Return on Equity in General Insurance Companies Registered in the Indonesian Insurance Directory for the 2018-2022 period. This study uses a quantitative approach with secondary data sources obtained from company financial reports issued by each company. The sampling technique in this study was to use purposive sampling so that 20 companies were selected based on the sample criteria. This research is a quantitative research using panel data regression analysis method with the help of eviews 10. The results showed that the Net Premium Growth Ratio and Underwriting Ratio had no and significant effect on Return on Equity, Solvency Margin Ratio and Investment Yield Ratio had a significant negative effect on Return on Equity.